Understanding online consumer behavior and eWOM strategies for sustainable business management in the tourism industry - Reyes-Menendez, Ana (2020)
Electronic word of mouth (eWOM) has been widely used by most consumers on di erent digital platforms. This review aimed to obtain further insights into online consumer behavior through social networking sites and online reviews sites to help tourism businesses develop sustainable eWOM strategies. To this end, an exploratory study was developed to analyze available literature on eWOM strategies and online consumer behavior. The systematic literature review analysis focused on the following two main topics: (i) tourism and (ii) eWOM. The scientific database, Web of Science, was used to collect relevant literature on the subject. The search terms “Tourism” and “eWOM” were used. Searching the database, Web of Science, yielded a total of 124 articles; upon application of di erent filters, a total of 14 studies were included in the final dataset. The results of the present study provide new insights into consumer behavior for social sciences and businesses for the adoption of sustainable strategies to increase the influence of eWOM on the tourism industry.